Some Features of Etiquette Speech Acts of the Russian Wedding Ceremony in the Aspect of the Formation of Pragmatic Competence of Chinese Students by the study of Russian language: Некоторые особенности этикетных речевых актов русского свадебного обряда в аспекте формирования прагматической компетенции китайских студентов при изучении русского языка - Yawei, Hu (Przegląd Wschodnioeuropejski, 2019)
The subject of the article is the problems of communicative behavior of students. As a result of studying the theoretical material and the practice of its application, an effective method of studying Russian by Chinese students through national features of speech etiquette. All this will increase the level of practical language skills. This article is devoted to the study of Russian as a foreign language on the example of ritual speech acts of the wedding rite in Russian culture. The author believes that the use of speech formulas of etiquette in the teaching of the Russian language will facilitate the effective assimilation of knowledge and the formation of pragmatic competence of students.